2022
DOI: 10.1155/2022/2828687
|View full text |Cite|
|
Sign up to set email alerts
|

The Impact of Tax Reduction and Fee Reduction Based on Big Data Algorithm on the High-Quality Development of the Real Economy under the Action of Coupling Effect or Substitution Effect

Abstract: The basic idea of the mass of medical growth is to adhere to local market price thinking with a Chinese touch and follow the development policy of “quality first, efficiency first.” It insists on properly handling a series of important relationships betwixt socialism and market economy, the first to drive the rich later, the government and the market, equality and efficiency, short-term growth and long-term development, China and the international economy, ecology and growth of the region. Under the guidance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…As the value-added tax reform has been in progress, the academic community has gradually shifted its focus to the study of the effects of cutting taxes and administrative fees. From a macroeconomic perspective, tax reduction promotes economic growth [ 11 , 12 ] and reduces the tax burden for most industries, including the real economy [ 13 ]. Njogu LK [ 14 ] used Kenyan national data to conclude that there is a significant negative correlation between the value-added tax rate and gross domestic product.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…As the value-added tax reform has been in progress, the academic community has gradually shifted its focus to the study of the effects of cutting taxes and administrative fees. From a macroeconomic perspective, tax reduction promotes economic growth [ 11 , 12 ] and reduces the tax burden for most industries, including the real economy [ 13 ]. Njogu LK [ 14 ] used Kenyan national data to conclude that there is a significant negative correlation between the value-added tax rate and gross domestic product.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Manda S, Bansal SK [ 40 ] believed that the potential positive economic outcomes of corporate tax cuts outweigh the negative ones, and that corporate tax cuts will help improve India’s competitiveness and cost of doing business in the global marketplace. Zhang H [ 13 ] concluded through his study that the real economy is getting better under the effect of tax reduction and fee reduction. Gechert S, Heimberger P [ 41 ] applied meta-regression methods to a new dataset and the results showed that corporate tax cuts promote economic growth.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%